PENGARUH STRATEGI JOYFUL LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS DI KELAS IV SD - Fauziyah, Mahmudatul; Galuh Kartika Dewi; Ery Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low learning outcomes of students indicate that there are obstacles in understanding the subject matter which can be caused by learning strategies that are less interesting to the level of student development. This study aims to determine the effect of the joyful learning strategies on learning outcomes and student responses in IPAS subject in class IV of elementary school. Quantitative studies using a quasi-experimental design were the ones that were employed. The study's control group design was a nonequivalent (pre- and post-test) type. Fourth graders from Darul Ulum Elementary School made up the study's population. The results showed that the control group had a mean score of pretest 69.39 and a posttest score of 83.39, lower than the mean score of the experimental group pretest 72.70 and posttest 88.09. The findings of the questionnaire and data analysis methods such as the independent sample t-test corroborate this difference. A significant value of 0.008 was obtained from the computation of the hypothesis test (T test). The null hypothesis (H0) is rejected due to the significant value of 0.008 <0.05, suggesting that students' IPAS learning results in fourth grade are influenced by joyful learning strategy. Similarly, when employing joyful learning, the student response questionnaire yielded an average score of 85%, indicating a positive reaction from the pupils.